PaP1, a Broad-Spectrum Lysin-Derived Cationic Peptide to Treat Polymicrobial Skin Infections - Heselpoth, Ryan D.; Euler, Chad W.; Fischetti, Vincent A. (Frontiers in Microbiology, 2022)
Most skin infections, including those complicating burns, are polymicrobial involving multiple causative bacteria. Add to this the fact that many of these organisms may be antibiotic-resistant, and a simple skin lesion or burn could soon become life-threatening. Membrane-acting cationic peptides from Gram-negative bacteriophage lysins can potentially aid in addressing the urgent need for alternative therapeutics. These peptides natively constitute an amphipathic region within the structural composition of these lysins and function to permit outer membrane permeabilization in Gram-negative bacteria when added externally. This consequently allows the lysin to degrade the peptidoglycan substrate, resulting in rapid hypotonic lysis and bacterial death. When separated from the lysin, some of these cationic peptides kill sensitive bacteria more effectively than the native molecule via both outer and cytoplasmic membrane disruption. In this study, we evaluated the antibacterial properties of a modified cationic peptide from the broad-acting lysin PlyPa01. The peptide, termed PaP1, exhibited potent in vitro bactericidal activity towards numerous high priority Gram-positive and Gram-negative pathogens, including all the antibiotic-resistant ESKAPE pathogens. Both planktonic and biofilm-state bacteria were sensitive to the peptide, and results from time-kill assays revealed PaP1 kills bacteria on contact. The peptide was bactericidal over a wide temperature and pH range, and could withstand autoclaving without loss of activity. However, high salt concentrations and complex matrices were found to be largely inhibitory, limiting its use to topical applications. Importantly, unlike other membrane-acting antimicrobials, PaP1 lacked cytotoxicity towards human cells. Results from a murine burn wound infection model using methicillin-resistant Staphylococcus aureus or multidrug-resistant Pseudomonas aeruginosa validated the in vivo antibacterial efficacy of PaP1. In these studies, the peptide enhanced the potency of topical antibiotics used clinically for treating chronic wound infections. Despite the necessity of additional research and drug development, the collective data from our study preliminarily supports PaP1 as a potential broad-spectrum monotherapy or adjunctive therapy for the topical treatment of polymicrobial infections, and provides a foundation for engineering future lysin-derived peptides with improved antibacterial properties.